Sexual dysfunction in women with diabetes mellitus - Miočić, Jelena (Array, 2008)
Summary: Sexual dysfunction may be one of the chronic complications in women with diabetes, thus deserving further research. This review provides a definition of sexual dysfunction, its pathophysiology, preclinical and clinical trials on the issue, diabetes as a metabolic syndrome and its impact on sexual dysfunction. The possible therapeutic interventions are described